Budget impact analysis of two treatment approaches for hepatitis C in Malaysia through the use of voluntary and compulsory licensing options - Azzeri, Amirah; Dahlui, Maznah; Mohamed, Rosmawati; McDonald, Scott Alexander; Jaafar, Hafiz; Shabaruddin, Fatiha Hana (Frontiers in Public Health, 2023)
Introduction A scaled-up treatment cascade with direct-acting antiviral (DAA) therapy is necessary to achieve global WHO targets for hepatitis C virus (HCV) elimination in Malaysia. Recently, limited access to sofosbuvir/daclatasvir (SOF/DAC) is available through compulsory licensing, with access to sofosbuvir/velpatasvir (SOF/VEL) expected through voluntary licensing due to recent agreements. SOF/VEL has superior clinical outcomes but has higher drug acquisition costs compared to SOF/DAC. A stratified treatment cascade might be the most cost-efficient approach for Malaysia whereby all HCV patients are treated with SOF/DAC except for patients with cirrhosis who are treated with SOF/VEL. Methods This study aimed to conduct a 5-year budget impact analysis of the proposed stratified treatment cascade for HCV treatment in Malaysia. A disease progression model that was developed based on model-predicted HCV epidemiology data was used for the analysis, where all HCV patients in scenario A were treated with SOF/DAC for all disease stages while in scenario B, SOF/DAC was used only for non-cirrhotic patients and SOF/VEL was used for the cirrhotic patients. Healthcare costs associated with DAA therapy and disease stage monitoring were included to estimate the downstream cost implications. Results The stratified treatment cascade with 109 in Scenario B was found to be cost-saving compared to Scenario A. The cumulative savings for the stratified treatment cascade was USD 1.4 million over 5 years. Discussion A stratified treatment cascade with SOF/VEL was expected to be cost-saving and can result in a budget impact reduction in overall healthcare expenditure in Malaysia.